Quantification in Experimental Psychology and Pragmatic Epistemology: Tension Between the Scientific Imperative and the Social Imperative - Guyon, Hervé (Frontiers in Psychology, 2021)
Our position is critical of the dominant method in psychology, and critical of the social use of psychological models. We assert that the scientific approach in psychology must break with modernist claim, but without sinking into post-modernist relativism. We consider that the epistemology associated with experimental psychology should be a specific epistemology associated with the particular objects studied. By calling on pragmatism and realism, psychology can find the resources to use quantitative studies as an action deployed within a complex, interactive and dynamic social space, and thus break with its normative practice and function.